AB1445-HPR Patient satisfaction in a rheumatoid arthritis outpatient centre. (12th June 2018) - Villarreal, L.; Buitrago-Garcia, D; Rodriguez, F.; Mendez, I.; Santos-Moreno, P.
Abstract : Background: Patient experience (PX) can be conceptualised as "the sum of all interactions, shaped by an organisation's culture, that influence patient perceptions, across the continuum of care" nowadays patient satisfaction is considered as one of the quality for performance in health systems(. 1 Rheumatology is mainly an outpatient, multidisciplinary medical specialty, therefore care does not stop at the diagnosis it continues during a long-term with frequent monitoring and patient participation. 2 Objectives: Describe the results of a patient satisfaction survey in a specialised centre in. Colombia during 2017 Methods: In our RA specialised centre during a 12 month period we performed a satisfaction survey in order to evaluate the health services provided. We evaluated the waiting times, timing on attention, appointment assignment, and information provided, the treatment received by the healthcare team, facilities among others. Patients evaluated the services provided in a scale from 1 to 5 were 1 was very bad, 2 bad, 3 regular 4 good and 5 very good. Descriptive epidemiology was performed for each variable presented. Results: We performed 4756 surveys during 2017, 4550 surveys were completed with a 95% rate response, out of total 80% of respondents were female and 20% male. 80% of patients reported to receive their appointments on time; regarding the service provided by our health care professionals 99% of patients understood the indications regarding their treatment, 98% understood about the administrative procedures to program future appointments and to how to access to their medications, also 98% had clearly understood the date and time of their consultation (rheumatologist, physical therapist, nutritionist, psychologist, infusion therapy, among others.) The mean score for the overall assessment of the services was 4.2/5.0 (table 1). The average time of stay at our centre was 60 min±33. The main aspects to improve our patient satisfaction were the telephone programming of appointments, and the compliance regarding the delivery of medications. Conclusions: This survey describes well-functioning multidisciplinary services for all patients who visit to our specialised centre. On the other hand although we found that our patients are highly satisfied, there is a large opportunity to improve our services and generate evidence regarding other aspects that involve the patient's health determinants. References: [1] Th VP. Creating the ideal patient experience. Journal of medicine and life. 2016;9(4):380–5. [2] Vare P, Nikiphorou E, Hannonen P, Sokka T. Delivering a one-stop, integrated, and patient-centered service for patients with rheumatic diseases. SAGE open medicine. 2016;4:2050312116654404. Disclosure of Interest: None declared